Early detection of whole body radiation induced microstructural and neuroinflammatory changes in hippocampus: A diffusion tensor imaging and gene expression study. Issue 4 (20th July 2016) - Gupta, Mamta; Mishra, Sushanta Kumar; Kumar, B.S. Hemanth; Khushu, Subash; Rana, Poonam
Abstract : Ionizing radiation is known to a cause systemic inflammatory response within hours of exposure that may affect the central nervous system (CNS). The present study was carried out to look upon the influence of radiation induced systemic inflammatory response in hippocampus within 24 hr of whole body radiation exposure. A Diffusion Tensor Imaging (DTI) study was conducted in mice exposed to a 5‐Gy radiation dose through a 60 Co source operating at 2.496 Gy/min at 3 hr and 24 hr post irradiation and in sham‐irradiated controls using 7 T animal MRI system. The results showed a significant decrease in Mean Diffusivity (MD), Radial Diffusivity (RD), and Axial Diffusivity (AD) in hippocampus at 24 hr compared with controls. Additionally, marked change in RD was observed at 3 hr. Increased serum C‐Reactive Protein (CRP) level depicted an increased systemic/peripheral inflammation. The neuroinflammatory response in hippocampus was characterized by increased mRNA expression of IL‐1β, IL‐6, and Cox‐2 at the 24 hr time point. Additionally, in the irradiated group, reactive astrogliosis was illustrated, with noticeable changes in GFAP expression at 24 hr. Altered diffusivity and enhanced neuroinflammatory expression in the hippocampal region showed peripheral inflammation induced changes in brain. Moreover, a negative correlation between gene expression and DTI parameters depicted a neuroinflammation induced altered microenvironment that might affect water diffusivity. The study showed that there was an influence of whole body radiation exposure on hippocampus even during the early acute phase that could be reflected in terms of neuroinflammatory response as well as microstructural changes. © 2016 Wiley Periodicals, Inc. Abstract : DTI and gene expression studies were conducted in mice at 3 and 24 hr following 5‐Gy whole body irradiation. The study shows a negative correlation between diffusivity and inflammatory gene expression in hippocampus, supporting the influence of a systemic inflammatory response to the brain microenvironment even during the early acute phase.